The Psychometric Properties of the Norwegian version of Eating Disorder Inventory, version 3 (EDI-3) - Kaiser, Sabine; Martinussen, Monica (PsykTestBarn, 2015)
Description: The Eating Disorder Inventory (EDI) was developed by Garner, Olmstead, and Polivy in 1983. It was translated into Norwegian by Øyvind Rø and Jan H. Rosenvinge. The third version of the EDI was published in 2004, and is a revised version of the EDI-2. The EDI-3 is a self-report instrument for adolescents from 13 years of age through adulthood, that measures symptoms and psychological features related to eating disorders, and consists of 91 questions divided into twelve subscales. Literature search: The literature search for Norwegian, Danish, and Swedish articles with information about the psychometric properties of the EDI-3 identified one Danish and one Swedish study. The psychometric properties, norms, and the factor structure of the questionnaire were examined among adult female patients with eating disorders and healthy women, representative for the female population in Denmark and Sweden. Psychometrics: Internal consistency was good to excellent for the twelve subscales, and ranged between .75 and .92 for patients based on the Danish clinical sample and between .70 and .92 based on the Swedish clinical sample. Confirmatory factor analysis was conducted and confirmed the factor structure for both the patient- and for the control group. The EDI-3 discriminated well between patients and controls, which strengthens the construct validity of the instrument. Sensitivity and specificity was very good to excellent for six of 12 subscales based on the Swedish sample. Conclusion: The literature search did not identify any psychometric studies of the EDI-3 in Norway. Therefore, we cannot say anything certain about the psychometric properties of the Norwegian test version. The test has been examined in Swedish and Danish samples with promising results regarding the psychometric properties. However, some differences were detected indicating a need for establishing Norwegian norms.